Hubungan Pola Makan Pagi dengan Status Gizi pada Mahasiswi Poltekkes Kemenkes Aceh - Ampera Miko; Putry Bela Dina (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
Eating patterns can be assessed directly on the quality and quantity of the dishes. If the composition of the dishes meets the body's needs, both quantity, and quality, then the body will have health conditions as well as possible and a good nutritional state can be achieved. This research is descriptive analytic design cross-sectional. Data on the diet of the morning that includes frequency of eating breakfast, the number of breakfast and types of breakfast collected using food frequency for 7 days through the distribution of questionnaires, the Body Mass Index was collected by weighing student using digital scales and measuring the height of student use microtia. Univariate and Bivariate data analysis using chi-square statistical test. The results of 53 respondents have on the students who have the nutritional status in the category of energy deficiency (20%) have a morning meal pattern in both categories compared to the category less (12.5%), while the student-nourished in the category of obesity largely (20,0%) are also present in the diet in the morning in both categories compared with the category of less little (6,25%). In the conclusion, there is no relationship between diet and nutritional status breakfast Aceh polytechnic student Ministry of Health. Suggested that the student can maintain a normal nutritional status and achieve normal nutritional status. Keywords: Breakfast Eating patterns, nutritional status, student